Development of SBR-Nanoclay Composites with Epoxidized Natural Rubber as Compatibilizer. (14th June 2009) - Rajasekar, R.; Heinrich, Gert; Das, Amit; Das, Chapal Kumar
Abstract : The significant factor that determines the improvement of properties in rubber by the incorporation of nanoclay is its distribution in the rubber matrix. The simple mixing of nonpolar rubber and organically modified nanoclay will not contribute for the good dispersion of nanofiller in the rubbery matrix. Hence a polar rubber like epoxidized natural rubber (ENR) can be used as a compatibilizer in order to obtain a better dispersion of the nanoclay in the matrix polymer. Epoxidized natural rubber and organically modified nanoclay composites (EC) were prepared by solution mixing. The nanoclay employed in this study is Cloisite 20A. The obtained nanocomposites were incorporated in styrene butadiene-rubber (SBR) compounds with sulphur as a curing agent. The morphology observed through X-ray diffraction (XRD) and high-resolution transmission electron microscopy (HR-TEM) shows that the nanoclay is highly intercalated in ENR, and further incorporation of EC in SBR matrix leads to partial exfoliation of the nanoclay. Dynamic mechanical thermal analysis showed an increase in storage modulus and lesser damping characteristics for the compounds containing EC loading in SBR matrix. In addition, these compounds showed improvement in the mechanical properties.